Utilization of the Theory of Planned Behavior for Analyzing the Issue of Throwing Garbage in Public Places - B.M.A.S. Anaconda Bangkara, (Jurnal Serambi Ilmu, 2024)
In 2015, the results of United Nations research called out Indonesia as the second-largest contributor to plastic waste in the ocean, following China. This problem was, absolutely, inseparable from improper waste disposal behavior. This recent research was intended to prove the theory of planned behavior in the issue of throwing garbage in public places. Variables included in this case were attitude, subjective norms, perceived behavioral control, and intention. Questionnaires were distributed online and offline to people who had thrown out their garbage in public places. A total of 396 respondents were obtained, and the Confirmatory Factor Analysis (CFA) method of the Structural Equation Model (SEM) was used in this research with IBM SPSS 25 and AMOS 24 tools. This research found that the good value of public place visitors’ attitudes would develop their intention of throwing garbage properly. Visitors misunderstood the function of the cleaning service officers. They considering that their garbage would be taken care of by the cleaning service officers. The availability of trash cans in public places would support the visitors’ behavior in managing their garbage.